Covid-19 pandemic awareness and coping strategies of cocoa farmers in Ondo State of Nigeria - Agulanna, Foluso Temitope (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
The study investigated COVID-19 pandemic awareness and coping strategies of cocoa farmers in Ondo State of Southwestern Nigeria. Random sampling technique was used to select cocoa farmers in the study area. A total of fifty cocoa farmers (respondents) were purposively selected from Ile-Oluji/Oke-Igbo local government area of the state. Information was collected from the selected farmers with the aid of well-structured questionnaires and the data retrieved from forty-six cocoa farmers collected were analysed with descriptive statistics and chi-square analysis. The result of the analysis showed that 76.1% of the farmers are above the age of 41 years, 78.3% are males while 76.1% are married. Similarly, 78.3% of the cocoa farmers have 4-6 children in the household, 26.1% had secondary education, 43.5% have 16 to 20 years farming experience while 73.9% lived in condominiums or housing units where residents are herded together thereby predisposing them to the risk of the contagion. Most of the respondents (95.7%) had low income or sales during covid-19 pandemic, 78.3% ate food three times before covid-19 while 15.2% ate three times during the pandemic. 89.1% did not have enough food at home during the lockdown and 95.6% did not have enough money to buy food during the pandemic. Majority of the respondents (96%) were aware of the occurrence of COVID-19, 69.6% of the respondents coped by relying on less expensive food during the lockdown, 56.5% reduced their food consumption due to income loss, 63% reduced the number of meals eaten daily while 67.4% reduced the portion or size of meal daily during COVID-19. The chi-square test also showed that a significant relationship exists between farmers’ awareness and coping strategies to covid-19 as well as the quality and type of food they consumed.